SOEP-IS 2016 - BIOPAREN: Biography information on the parents - DIW Berlin / SOEP (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
The aim of the data file BIOPAREN is to make the biography entries on the parents and on the social origin of the respondent available.
Keywords: 330